2016
DOI: 10.3109/00952990.2016.1167898
|View full text |Cite
|
Sign up to set email alerts
|

DUI recidivism by intervention adherence: a multiple risk factor approach

Abstract: The MASEP participants who were adherent with the intervention were significantly less likely to recidivate than those who were non-adherent. However, variance in the multi-component intervention completion rates suggests that the program resonates better with specific population subsets. We argue for researchers and policymakers to further explore how specific population subsets react to varying intervention programs to maximize efforts to reduce impaired driving.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…It is important to note that although age groups that started out with relatively more problematic characteristics generally evidenced more pre–post positive change, in many cases, they did not “catch up” to the other age groups. Given that younger adults are more likely to recidivate after a first DUI offense than older individuals (Impinen et al, ; Robertson, ), the results of this study suggest that providers of indicated prevention for harmful substance use in younger individuals may need to focus more attention on or develop novel strategies to enhance gains related to risk perception and intentions to engage in high‐risk behavior.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…It is important to note that although age groups that started out with relatively more problematic characteristics generally evidenced more pre–post positive change, in many cases, they did not “catch up” to the other age groups. Given that younger adults are more likely to recidivate after a first DUI offense than older individuals (Impinen et al, ; Robertson, ), the results of this study suggest that providers of indicated prevention for harmful substance use in younger individuals may need to focus more attention on or develop novel strategies to enhance gains related to risk perception and intentions to engage in high‐risk behavior.…”
Section: Discussionmentioning
confidence: 87%
“…Recidivists account for a large proportion of DUI arrests, with up to one third of those arrested for DUI being rearrested for the same offense (Impinen et al, ). Moreover, younger drivers are more likely to recidivate than older drivers (Impinen et al, ; Robertson, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Robertson, Gardner, Walker and Tatch () revealed that people with a DUI who comply with program requirements are significantly less likely to reoffend within 3 years. This suggests that—in addition to a clear need for development and empirical evaluation of DUI educational programming to offer the field with guidance for best practices—both policy makers and developers of DUI education programs must better understand how to engage DUI offenders to increase compliance rates.…”
Section: Factors To Consider In Developing Dui Programmingmentioning
confidence: 99%
“…The key goal of DUI educational programming is to prevent recidivism; therefore, understanding the characteristics of DUI recidivists will help to target curricular interventions. For example, men are significantly more likely to be repeat offenders than women (Robertson et al, ). Furthermore, compared with first‐time offenders, recidivists are more likely to be older, use drugs other than alcohol, and have psychiatric comorbidity (Nelson, Belkin, LaPlante, Bosworth, & Shaffer, ).…”
Section: Predictors Of Dui Recidivismmentioning
confidence: 99%